Revisiting the spectrum of lower motor neuron diseases with snake eyes appearance on magnetic resonance imaging. (22nd May 2014) - Lebouteux, M.‐V.; Franques, J.; Guillevin, R.; Delmont, E.; Lenglet, T.; Bede, P.; Desnuelle, C.; Pouget, J.; Pascal‐Mousselard, H.; Pradat, P.‐F.
<x xml:space="preserve">Abstract</x> Background and purpose The 'snake eyes' sign refers to bilateral hyperintensities of the anterior horns on axial spinal cord imaging. Based on sporadic reports, it has been associated with a range of lower motor neuron (LMN) syndromes, such as spondylotic amyotrophy and Hirayama disease, as well as spinal cord infarction. The objective of our study was to comprehensively characterize the full diagnostic spectrum of LMN syndromes with this radiological clue and discuss potential aetiological factors. Methods A large patient cohort with snake eyes sign and upper limb LMN degeneration was recruited from three French neuromuscular units. Patients underwent detailed electrophysiological, radiological, clinical and anamnestic profiling. Results Twenty‐nine patients were ascertained and followed up for 9.5 ± 8.6 years. The majority of the patients were male (86.2%) with a mean age of 37.3 ± 14.4 years. Symptoms were bilateral in most cases (86.2%). Patients with predominantly proximal and distal deficits were equally represented (44.8% and 55.2%, respectively). A history of preceding trauma or intense physical activity was confirmed in 58.6% of the cases; 27.6% of the patients were given an initial clinical diagnosis of amyotrophic lateral sclerosis (ALS), and 51.7% were originally suspected to have multifocal motor neuropathy. None of the patients developed ALS on longitudinal follow‐up. Conclusion The snake eyes sign on magnetic resonance imaging is associated with a wide spectrum of neurological conditions and is more common in young men with a history of strenuous activity or antecedent trauma. The recognition of this syndrome is crucial as many of these patients are initially misdiagnosed with ALS.